Symbolic Efficacy in the Psychiatric Ward: A Clinical Ethnography of Cetik-Attributed Psychosis and Hospital-Facilitated Ritual Integration in Bali - Ni Wayan Saka Rahayu; Ni Made Citra Riesti Wulan; Nyoman Ari Yoga Wirawan; Ida Bagus Ngurah Dwipayana Manuaba (Enigma in Cultural, 2025)
In Bali, acute psychosis is frequently interpreted through the Niskala or unseen cosmology, specifically attributed to Cetik or magical poisoning and Guna-guna or sorcery. This explanatory model often clashes with biomedical paradigms, leading to poor therapeutic alliance and treatment refusal. This study aims to evaluate the pathoplastic efficacy and symbolic healing mechanisms of an integrative therapeutic approach. We employed a clinical ethnography design within a psychiatric ward in Denpasar, Bali. The subject was a 26-year-old Balinese female with Acute and Transient Psychotic Disorder (ICD-10: F23.2), presenting with severe psychomotor agitation (PANSS-EC score of 22). Data were collected via the DSM-5 Cultural Formulation Interview (CFI), non-participant observation of a hospital-facilitated Penglukatan or purification ritual, and clinical timeline mapping. We utilized a rigorous reflexivity framework to analyze the intersection of the clinical gaze of the psychiatrist and the ritual authority of the Balian or traditional healer. The distress of the patient was culturally coded as "spiritual heat" or Panes resulting from Cetik ingestion. A timeline analysis revealed a significant reduction in psychomotor agitation, with the PANSS-EC score dropping from 22 to 10, occurring 30 minutes post-ritual but prior to the administration of oral Risperidone. This temporal dissociation suggests the immediate behavioral containment was mediated by cultural symbolic efficacy rather than pharmacological dopamine blockade. In conclusion, the Balian functioned as a "cultural broker," transforming the "contaminated" hospital space into a sanctuary. Future research should quantify this effect through randomized controlled trials comparing standard care against integrated ritual care. Policy reform should focus on institutionalizing spiritual visitation protocols akin to chaplaincy services.